Tolbutamide induces conformational change and promotes albumin glycation - Bansode, Sneha B.; Batkulwar, Kedar B.; Warkad, Shrikant D.; Jana, Asis K.; Sengupta, Neelanjana; Kulkarni, Mahesh J. (RSC Advances, 2015)
Tolbutamide is a first generation sulfonylurea drug used for the treatment of type II diabetes. In the present study, the effect of tolbutamide on albumin conformation was investigated using BSA as a model protein. The binding of tolbutamide induced a conformational change in albumin, which was confirmed by thioflavin T assay, ANS assay, and CD spectroscopy. Computer simulations suggested that the binding of tolbutamide increases the solvent accessibility of lysine residues, the hotspots of glycation. Furthermore, the change in conformation of albumin facilitates increased glycation, which was observed by AGE specific fluorescence and the results were corroborated by mass spectrometric analysis. This study suggested that tolbutamide enhances albumin glycation by inducing conformational change in BSA and hence could be a potential risk factor if used for a prolonged period.

Targeted quantification of N-1-(carboxymethyl) valine and N-1-(carboxyethyl) valine peptides of beta-hemoglobin for better diagnostics in diabetes - Jagadeeshaprasad, Mashanipalya G.; Batkulwar, Kedar B.; Meshram, Nishita N.; Tiwari, Shalbha; Korwar, Arvind M.; Unnikrishnan, Ambika G.; Kulkarni, Mahesh J. (Clinical Proteomics, 2016)
Background: N-1-(Deoxyfructosyl) valine (DFV) beta-hemoglobin (beta-Hb), commonly referred as HbA1c, is widely used diagnostic marker in diabetes, believed to provide glycemic status of preceding 90-120 days. However, the turnover of hemoglobin is about 120 days, the DFV-beta-Hb, an early and reversible glycation product eventually may undergo irreversible advanced glycation modifications such as carboxymethylation or carboxyethylation. Hence quantification of N-1-(carboxymethyl) valine (CMV) and N-1-(carboxyethyl) valine (CEV) peptides of beta-Hb would be useful in assessing actual glycemic status. Results: Fragment ion library for synthetically glycated peptides of hemoglobin was generated by using high resolution-accurate mass spectrometry (HR/AM). Using parallel reaction monitoring, deoxyfructosylated, carboxymethylated and carboxyethylated peptides of hemoglobin were quantified in clinical samples from healthy control, pre-diabetes, diabetes and poorly controlled diabetes. For the first time, we report N-1-beta-valine undergoes carboxyethylation and mass spectrometric quantification of CMV and CEV peptides of beta-hemoglobin. Carboxymethylation was found to be the most abundant modification of N-1-beta-valine. Both CMV-beta-Hb and CEV-beta-Hb peptides showed better correlation with severity of diabetes in terms of fasting glucose, postprandial glucose and microalbuminuria. Conclusions: This study reports carboxymethylation as a predominant modification of N-1-beta-valine of Hb, and quantification of CMV-beta-Hb and CEV-beta-Hb could be useful parameter for assessing the severity of diabetes.
Keywords: Diabetes; Diagnosis; Glycation; Glycemic control; HbA1c; Mass spectrometry

Targeted quantification of the glycated peptides of human serum albumin - Garikapati, Vannuruswamy; Korwar, Arvind M.; Jagadeeshaprasad, Mashanipalya G.; Kulkarni, Mahesh J. (Methods in Molecular Biology, 2017)
Glycated human serum albumin (HSA) serves as an important marker for monitoring the glycemic status. Developing methods for unambiguous identification and quantification of glycated peptides of HSA using high-throughput technologies such as mass spectrometry has a great clinical significance. The following protocol describes the construction of reference spectral libraries for Amadori-modified lysine (AML), N(ε)-(carboxymethyl) lysine (CML)-, and N(ε)-(carboxyethyl)lysine (CEL)-modified peptides of synthetically modified HSA using high-resolution mass spectrometers. The protocol also describes work flows, for unambiguous identification and quantification of glycated modified peptides of HSA in clinical plasma using standard spectral libraries by various mass spectrometry approaches such as parallel reaction monitoring (PRM), sequential window acquisition of all theoretical fragment ion spectra (SWATH), and MSE.

Tubulointerstitial nephritis antigen-like 1 protein is downregulated in the placenta of pre-eclamptic women - Mary, Sheon; Kulkarni, Mahesh J.; Mehendale, Savita S.; Joshi, Sadhana R.; Giri, Ashok P. (Clinical Proteomics, 2017)
Background: Tubulointerstitial nephritis antigen-like 1 protein (TINAGL1), is a matricellular protein, known to play role in cell adhesion and cell receptor interaction. Research related to TINAGL1 is limited to cell culture and animal models. Demonstration of TINAGL1 as a positive regulator of angiogenesis and its expression in the decidua of postimplantation mouse uterus, prompted us to validate its expression in human placenta during impaired angiogenesis in pre-eclamptic condition. Methods: Placental tissue from normotensive (n = 25) and pre-eclamptic (n = 25) pregnancies were used to study the differentially expressed proteins by two-dimensional gel electrophoresis and TINAGL1 protein was validated with Western blotting. Results: A total of 55 protein spots were differentially expressed (fold change > 1.5, p < 0.05), of which 27 were upregulated and 28 were downregulated in the pre-eclamptic placenta. TINAGL1 was found to be downregulated in pre-eclamptic compared to normotensive pregnant women. Conclusion: This is the first study reporting TINAGL1 to be present in human placenta and differentially expressed in pre-eclamptic condition. The functional role of TINAGL1 in association to human pregnancy needs to be explored further.

Triton X-114 fractionated subcellular proteome ofleptospira interrogansshows selective enrichment of pathogenic and outer membrane proteins in the detergent fraction - Thoduvayil, Sikha; Dhandapani, Gunasekaran; Brahma, Rahul; Devasahayam Arokia Balaya, Rex; Mangalaparthi, Kiran K.; Patel, Krishna; Kumar, Manish; Tennyson, Jebasingh; Satheeshkumar, P. K.; Kulkarni, Mahesh J.; Pinto, Sneha M.; Prasad, T. S. Keshava; et al. (Proteomics, 2020)
The Triton X-114-based solubilization and temperature-dependent phase separation of proteins is used for subcellular fractionation where, aqueous, detergent, and pellet fractions represents cytoplasmic, outer membrane (OM), and inner membrane proteins, respectively. Mass spectrometry-based proteomic analysis of Triton X-114 fractions of proteomic analysis ofLeptospira interrogansidentified 2957 unique proteins distributed across the fractions. The results are compared with bioinformatics predictions on their subcellular localization and pathogenic nature. Analysis of the distribution of proteins across the Triton X-114 fractions with the predicted characteristics is performed based on ``number'' of unique type of proteins, and ``quantity'' which represents the amount of unique protein. The highest number of predicted outer membrane proteins (OMPs) and pathogenic proteins are found in aqueous and pellet fractions, whereas detergent fraction representing the OM has the highest quantity of OMPs and pathogenic proteins though lower in number than the aqueous and pellet fractions. This leaves the possibility of an upsurge in pathogenic proteins and OMPs on the OM under pathogenic conditions suggesting their potential use to combat leptospirosis. Further, the Triton X-114 subcellular fractions are more correlated to enrichment of pathogenic proteins predicted by MP3 software than predicted localization.
Keywords: intensity-based absolute quantification; Leptospira; outer membrane protein; subcellular localization; Triton X-114